ENHANCING STUDENTS’ LISTENING SKILL THROUGH QUIZIZZ AUDIO FEATURE IN ONLINE LEARNING AT JIARAWANON-UTIS 4 SCHOOL - Annisatul Fadlilah; Ulfatul Ma’rifah (Universitas PGRI Semarang, 2022)
The most challenging skill for EFL learners, especially in online learning is listening. As a result, an effective teaching tool is required to improve student's listening skills and motivation. This research aim is to describe how second graders students at Jiarawanon-Utis 4 School in Loei Province, Thailand used the Quizizz Audio Feature to enhance their listening skills. Eight students from the first semester of the school year 2021-2022 took part in this study. CAR (Classroom Action Research) was conducted in this study divided into two cycles. Each cycle consists of three meetings and four steps; planning, action, observation, and reflection. Data collection were collected from listening test, quizziz, observation, and questionnaires. Then triangulation is needed to evaluate the data. The result showed that there was an improvement in students’ listening skills. It is proven from the result of the average of both cycles. The average is 70,81% in the first cycle and 90,24% in the second cycle, so the enhancement is 19,43%. Furthermore, the findings of the questionnaires revealed that students gave excellent feedback regarding the use of the Quizizz Audio Feature to enhance their listening skills, as evidenced by their responses to the survey